Predictive value of phosphorylated axonal neurofilament subunit H for clinical outcome in patients with acute intracerebral hemorrhage - Cai, Jian-Yong; Lu, Chuan; Chen, Mao-Hua; Ba, Hua-Jun; Chen, Xian-Dong; Lin, Jian-Hu; Sun, Jun (Clinica chimica acta, 2013)
Phosphorylated axonal neurofilament subunit H (pNF-H) is a biomarker of axonal injury. We investigated whether plasma pNF-H concentrations were associated with 6-month clinical outcomes and early neurological deterioration (END) of patients with acute intracerebral hemorrhage. Plasma pNF-H concentrations of 112 patients and 112 healthy individuals were quantified by ELISA. Unfavorable outcome was defined as modified Rankin Scale score >2. Associations of plasma pNF-H concentrations with END, 6-month mortality and unfavorable outcome were evaluated. Plasma pNF-H concentrations were increased in patients than in healthy individuals [700.2 (430.8) pg/ml vs. 25.5 (32.4) pg/ml, P<0.001]. A logistic regression analysis selected plasma pNF-H concentration as an independent predictor for 6-month mortality [OR: 1.287, 95% CI: 1.140–1.524, P<0.001], 6-month unfavorable outcome (OR 1.265, 95% CI 1.121–1.517, P<0.001) and END (OR 1.246, 95% CI 1.109–1.498, P<0.001). A receiver operating characteristic curve analysis showed that plasma pNF-H concentration predicted 6-month clinical outcomes and END with high area under curves (all P<0.001). The predictive value of pNF-H was similar to that of the National Institutes of Health Stroke Scale score (all P>0.05). In a combined logistic-regression model, pNF-H did not improve the predictive value of National Institutes of Health Stroke Scale score (all P>0.05). Increased plasma pNF-H concentration was highly associated with 6-month clinical outcomes and END of patients with intracerebral hemorrhage. •pNF-H was released after acute intracerebral hemorrhage.•pNF-H was an independent predictor for long-term outcome and early neurological deterioration.•pNF-H has high predictive value for long-term outcome and early neurological deterioration.